Study on pharmacokinetic and tissue distribution of hyperin, astragalin, kaempferol-3-O-β-D-glucuronide from rats with multiple administrations of Semen Cuscutae processed with salt solution with effect of treating recurrent spontaneous abortion - Yang, Zhitong; Chen, Kaiwen; Zhang, Yuting; Xu, Baiyang; Huang, Yu; Zhang, Xue; Liu, Zilu; Wang, Tongsheng; Wu, Deling; Peng, Tangyi; Lu, Tulin; Cai, Hao; et al. (Frontiers in Pharmacology, 2024)
Semen Cuscutae (SP) is a traditional Chinese medicine that tonifies the kidneys and prevents miscarriage. According to Chinese medicine theory, kidney deficiency is one of the main causes of recurrent spontaneous abortion (RSA). The previous studies showed that SP and Semen Cuscutae processed with salt solution (YP) have ameliorative effects on RSA, and that YP is superior to SP. However, the active components of YP to ameliorate RSA remain unclear and require further studies. The objective of this study is to investigate the active components of YP in ameliorating RSA. First, a rat model of RSA was established using hydroxyurea in combination with mifepristone. Aqueous decoction of YP was given by gavage to rats. Second, pregnant rats were sampled on days 5, 7, 9, 10 and 12 during the modelling period. The content of hyperin (HY), astragalin (AS) and kaempferol-3-O-β-D-glucuronide (KA) in blood and liver, heart, spleen, lung and kidney tissues were detected by liquid chromatography-mass spectrometry (LC-MS). The pharmacodynamic indicators including progesterone (P), chorionic gonadotropin β (β-HCG), estradiol (E2), tumor necrosis factor-α (TFN-α), interleukin 4 (IL-4), and tryptophan (TRP) were measured by enzyme-linked immunosorbent assay (ELISA) Pearson's correlation analysis and grey relational analysis were used to establish the relationship between the pharmacodynamic indexes and chemical constituents. The pharmacokinetic results showed that the area under curve (AUC) value of KA was the largest. The tissue distribution results showed that astragalin was widely distributed in liver, heart, spleen, lung and kidney in the RSA model rats, while HY was detected only in the uterus, and KA was detected only in the kidney. The pearson correlationl analysis showed that KA was significantly and positively correlated with the contents of E2, P, β-HCG and TRP. Both AS and HY were significantly negatively correlated with the content of TNF-α, respectively. This study reveals the pharmacokinetics and tissue distribution of KA, AS and HY in rats with RSA. It was elucidated that all three were involved in the regulation of progesterone levels and immune function.The main active components of YP has been identified, and it provided a theoretical basis for the quality assessment of YP.